94.1k views
5 votes
Which equation is equivalent to - 2x + 5 - 3x = 5x + 25?A. -5 = -30B. -6x + 5 = 5x + 25C. - 10x = 20D. 20x - 5 = 25

1 Answer

3 votes

In order to determine which is the equivalent equation, simplify the given expression:

-2x + 5 - 3x = 5x + 25 simplify like terms left side

-2x - 3x + 5 = 5x + 25

-5x + 5 = 5x + 25 subtract 5x both sides and subtract 5 both sides

-5x - 5x = 25 - 5 simplify both sides

-10x = 20

Hence,the equivalent expression is -10x = 20

User Nimeshka Srimal
by
4.8k points